2005
DOI: 10.1051/0004-6361:20053798
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray continuum emission from the inner Galactic region as observed with INTEGRAL/SPI

Abstract: The diffuse continuum emission from the Galactic plane in the energy range 18-1000 keV has been studied using 16 Ms of data from the SPI instrument on INTEGRAL. With such an exposure we can exploit the imaging properties of SPI to achieve a good separation of point sources from the various diffuse components. Using a candidate-source catalogue derived with IBIS on INTEGRAL and a number of sky distribution models we obtained spectra resolved in Galactic longitude. We can identify spectral components of a diffus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 39 publications
7
101
4
Order By: Relevance
“…15). It should be noted that the observed cutoff in the GRXE spectrum above 60 keV does not agree with the unresolved hard X-ray excess reported by Strong et al (2005) and Bouchet et al (2005) in the SPI data. The reason for this discrepancy is not yet understood.…”
Section: Spectrumcontrasting
confidence: 67%
See 1 more Smart Citation
“…15). It should be noted that the observed cutoff in the GRXE spectrum above 60 keV does not agree with the unresolved hard X-ray excess reported by Strong et al (2005) and Bouchet et al (2005) in the SPI data. The reason for this discrepancy is not yet understood.…”
Section: Spectrumcontrasting
confidence: 67%
“…Lebrun et al (2004) and Terrier et al (2004) using IBIS telescope (Ubertini et al 2003) have shown that although bright point sources dominate the emission from the Galaxy at 30 keV, there is a significant unresolved component. Bouchet et al (2005) and Strong et al (2005) using SPI spectrometer (Vedrenne et al 2003) found an unresolved Galactic X-ray emission at energies higher than 50 keV.…”
Section: Introductionmentioning
confidence: 99%
“…The 20-100 keV LC of V404 as well as the other sources in the field were obtained in bins of 400 s. Background models were built based on the pre-flaring data of a representative empty sky region, adjusting the normalization coefficient per hour (see, e.g., Strong et al 2005, for a more general description of the method).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…This electron spectrum and distribution were chosen to approximately yield the observed synchrotron Haze. For comparison, we also show the measurements of the diffuse gamma ray spectrum from this region, as measured by EGRET [12]. Shown as dotted lines is the much smaller and negligible contribution from Bremsstrahlung radiation.…”
Section: Gamma Rays Synchrotron and Inverse Compton Photons Frommentioning
confidence: 99%